Biomasa y carbono almacenado en las especies comerciales del bosque de colina baja de la concesión forestal N° 16-LOR-MAY/CON-MAD-2018-004, distrito de Mazán, Loreto. 2022 - Pacaya Perea, Ary Gissell (2023)
The biomass and the carbon stored in commercial species of a low-hill forest in the district of Mazán, Loreto, Peru were quantified. Data from the forest census of the commercial species of the operational plan (PO)1 of the cutting plot (PC) 1 of the forest concession contract No. 16-LOR-MAY/CON-MAD-2018-004 for timber purposes was evaluated. The results show a total dry biomass of 41 011,92 kg/ha, where Parkia ulei contributes with the highest biomass of 4785,02 kg/ha and Diplotropis martiusii with 2485,50 kg/ha. The diameter class from 70 cm to 80 cm contains the higher amount of dry biomass of 11 511,07 kg/ha and from 60 cm to 70 cm of 10 079,08 kg/ha. The stored carbon is 20,51 tC/ha, where Parkia ulei contains the higher amount of 2,39 tC/ha and Diplotropis martiusii of 1,24 tC/ha. The diameter class from 70 cm to 80 cm contains 5,76 tC/ha of stored carbon of and from 60 cm to 70 cm contains 5,04 tC/ha. A significant statistical difference (α = 0,05) between the biomass and stored carbon averages was found.